Findings of an observational investigation of pure remote follow-up of pacemaker patients: is the in-clinic device check still needed?. (1st October 2016) - Facchin, D.; Baccillieri, M.S.; Gasparini, G.; Zoppo, F.; Allocca, G.; Brieda, M.; Verlato, R.; Proclemer, A.
Abstract: Background: Device follow-up is mandatory in the care of patients with a pacemaker. However, in most cases, device checks appear to be mere technical, time-consuming procedures. The aim of this research is to evaluate whether remote follow-up can replace in-clinic device checks by assessing clinical outcomes for pacemaker patients followed only via remote follow-up. Methods and results: Consecutive pacemaker patients followed with remote monitoring were prospectively included by 6 Italian cardiology centers in an observational investigation. The workflow for remote monitoring included an initial assessment by nursing staff and, when necessary, by a responsible physician for medical decisions. No in-person visits were scheduled after the start of remote monitoring. One-thousand and two-hundred and fifty one patients (30% female, 75 ± 11 years old) were followed for a median observation period of 15 months. Out of 4965 remote transmissions, 1882 (38%) had at least one clinically relevant event to be investigated further, but, only after 137 transmissions (2.8%), the patients were contacted for an in-clinic visit or hospitalization. Sixty-nine patients died and 124 were hospitalized for various reasons. Atrial fibrillation episodes were the most common clinical events discovered by remote transmissions, occurring in 1339 (26%) transmissions and 471 (38%) patients. Conclusions: Our experience shows that remote monitoring in a pacemaker population can safely replace in-clinic follow-up, avoiding unnecessary in-hospital device follow-up.